Generative AI and Copyright Law: A Rule of Law Comparison between Indonesia and South Korea - Ruhtiani, Maya; Tri Naili, Yuris; Nurul Hidayah, Astika; Kyung Park, Hyun (Kosmik Hukum, 2025)
The advancement of generative artificial intelligence (AI) presents significant legal challenges to modern copyright systems, particularly in redefining originality and authorship in relation to AI-generated works. This study critically examines how copyright law in Indonesia and South Korea addresses these challenges through the normative lens of the rule of law. It explores how generative AI disrupts conventional legal concepts, especially concerning authorship attribution, ownership, and the legitimacy of protecting non-human creations under copyright. Using a normative juridical method, the research applies statutory, conceptual, and theoretical approaches to analyze the comparative legal responses of both countries. The focus is on the presence or absence of specific legal frameworks governing AI-generated content and their implications for legal certainty, distributive justice, and the adaptability of copyright law in the face of technological change. Findings show that Indonesia’s Copyright Law Number 28 of 2014 remains centered on a human authorship model and has yet to address the complexities introduced by digital innovation. Conversely, South Korea demonstrates a more progressive legal posture, reflected in its legislative discourse and policy developments regarding AI-assisted works and exceptions for text and data mining. The study concludes that Indonesia must initiate legal reform to align its copyright system with the evolving nature of authorship in the digital era. This reform should be grounded in the principles of the rule of law to ensure the protection of both moral and economic rights of creators in an increasingly AI-driven creative landscape. This research provides timely insights for policymakers and legal scholars navigating the intersection of copyright law and artificial intelligence, emphasizing the urgent need for adaptive legal frameworks in the age of artificial creativity.